Postage stamps as a means of propaganda to promote eye examination and vision screening - K. V. Troianovska; Andrii Korol; O. M. Blavatska; I. I. Zheltvai (Ukrainian Society of Ophthalmologists, 2023)
This paper deals with representation of eye examination and eye disease prevention methods in philately. The work represents the primary methods used for eye disease diagnosis and demonstrates the role of stamps in raising awareness among people regarding basic medical knowledge. The article is supplied with illustrative material, explanatory descriptions and comments.